(untitled) (CIPEEX, 2025)
Introduction: Valuing women health workers in Brazil’s Unified Health System (SUS) is inseparable from protecting mental health and preventing work-related violence. Objective: To synthesize policies and evidence to identify actionable strategies that strengthen recognition, safety, and well-being for women in the SUS workforce. Methods: An integrative review of Brazilian worker-health and mental-health policies within SUS and international guidelines on violence against women health workers, limited to publications from the past 10 years due to the lack of recent policy updates in this area, indexed in BVS, SciELO, and PubMed. Results: The synthesis identifies recurrent psychosocial risks—high emotional demands, moral harassment (workplace bullying), sexual harassment, and verbal and physical aggression—exacerbated by precarious contracts, night work, and weak incident-reporting systems. Effective measures cluster into four pillars: (1) governance: implementation of comprehensive worker-health policies with gender-responsive planning, routine risk assessment, and reliable reporting channels; (2) primary and specialized support: linkage of occupational health services with the Psychosocial Care Network to ensure rapid access to mental-health care and structured return-to-work plans; (3) safe work environments: team-based workflows, adequate staffing and security, and zero-tolerance protocols aligned with international frameworks; and (4) recognition and retention: career progression, fair pay, leadership opportunities, and supervision that reduces the stigma around help-seeking. Conclusions: To truly value women workers in SUS, management should integrate mental-health care and violence prevention into everyday work organization, guarantee decent working conditions and enforceable protections, and monitor outcomes; such measures are expected to reduce burnout and turnover while improving care quality, patient safety, and equity.